WAHDAT AL-WUJUD IN SERAT WEDHATAMA: HISTORICAL ROOTS, JAVANESE CONTEXTUALIZATION, AND ONTOLOGICAL REPRESENTATION - Mochammad Nginwanun Likullil Mahamid (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
The concept of Wahdat al-Wujud or the unity of being between humans and God is one of the central teachings in Sufism, which was systematically formulated by Ibn 'Arabi but has roots in earlier Sufi thought, such as Abu Yazid al-Busthami and al-Hallaj. Although widely accepted among Sufis, this concept has drawn theological criticism from figures such as Ibn Taymiyyah. In Java, this teaching entered through the scholarly channels from Andalusia–Middle East–Gujarat–Indonesian archipelago in the 15th/16th century, then adapted to local traditions influenced by the Kapitayan and Hinduism-Buddhism, forming a syncretic “Javanese Islam.” This study aimed to analyze the representation of Wahdat al-Wujud in the Serat Wedhatama by KGPAA Mangkunegara IV, focusing on symbolism, worship practices, and ontological perspectives. The method used was descriptive-analytical with a socio-linguistic approach, utilizing Ibn 'Arabi's Sufism theory and the framework of categorizing existence in mantiq. This study hypothesized that Serat Wedhatama not only adopted the concept of Wahdat al-Wujud theoretically, but also integrated it into the local wisdom of the palace through language, symbols, and spiritual practices typical of Javanese culture, thus creating a unique and contextual form of understanding.